Changes in leaf size and in the rate of leaf production contribute to cytokinin-mediated growth promotion in Epipremnum aureum L. cuttings - Di Benedetto, Adalberto; Galmarini, Claudio Romulo; Tognetti, Jorge (2018)
The growth of ornamental foliage plants is often limited by pot size, which exerts a restriction on root growth and, therefore, on the production of root-synthesised cytokinins which play key regulatory roles in the development and growth of the shoot. We studied the effect of exogenous 6-benzylaminopurine (BAP) on plant growth and on the development of leaf area in Epipremnum aureum L. plants grown in pots. The hypothesis was that increasing the concentration of shoot cytokinins by foliar spraying of BAP would promote plant growth by overcoming the effects of root restriction on whole plant development. Three glasshouse experiments were conducted using (i) different concentrations of BAP, (ii) different numbers of spray applications, and (iii) different light environments. The results showed that a single spray application of BAP at 5 mg l–1 significantly (P ≤ 0.05) increased leaf area (by 20 – 40%) and biomass [fresh weight (FW)] accumulation (by 30 – 35%), while higher BAP concentrations, or repeated spray applications had less effect. The maximum effect of BAP was observed under intermediate levels of irradiance. The increased development of leaf area in BAP-sprayed plants resulted from increases in both individual average leaf areas (by 100 – 150% cf. the controls) and the rate of leaf initiation (by 30 – 120% cf. the controls). The latter could be attributed to a shortening of the phyllochron, since no branching was observed under any BAP spray treatment. Alternative physiological explanations, as well as possible commercial applications of these BAP-elicited responses are discussed.